Patient perspective on living with mild hemophilia in Germany: results from a nationwide survey - Alesci, Rosa Sonja; Goldmann, Georg; Halimeh, Susan; Holstein, Katharina; Königs, Christoph; Miesbach, Wolfgang; Pfrepper, Christian; Olivieri, Martin (Frontiers in Medicine, 2024)
Introduction The disease burden and bleeding risk of patients with mild hemophilia may be underestimated. Their health-related quality of life (QoL) may be negatively impacted by insufficient treatment and bleed-related joint damage connected to a potentially delayed diagnosis. Aim This study aims to gain information on the care reality and QoL of patients aged ≥12 years with mild hemophilia in Germany. Methods An anonymous cross-sectional patient survey using standardized questionnaires was conducted in a validated electronic patient-reported outcome system. Medical specialists, hemophilia centers, patient organizations, and support groups across Germany invited the patients. Results A total of 43 patients (35 patients with hemophilia A, 5 patients with hemophilia B, and 3 patients for whom the information was missing) with a median age of 33 years were analyzed. The median age at diagnosis was 6.0 years (interquartile range [IQR] 2.0–15.0), and the median factor activity was 14.0% (IQR 12.0–25.0). Nearly 85% of the patients received factor concentrates in the past, and the most common reasons for the treatment were surgery or joint bleeding (each 65.6%). Half of the patients who provided feedback experienced complications during bleeding episodes. Prophylactic treatment with factor concentrates was rare (10.3%). The patients had minor problems regarding their health status. Conclusion Bleeding complications and joint bleeding, in particular, may be highly underestimated in patients with mild hemophilia, highlighting a medical need in this population. Patients with a potential benefit from prophylaxis need to be identified. Mild hemophilia has a negative impact on patients’ QoL. Hemophilia centers satisfied the patients’ needs. Further research is needed to address the current lack of awareness and improve adequate treatment in the future.